Hydroureteronephrosis due to a misplaced suprapubic catheter - Pranabh Kushwaha; Abhinav Kumar; Narendra Choudhary; Pratyusha Priyadarshini (Urology Case Reports)
Unintentional ureteral catheterisation, especially during the placement of suprapubic catheters, is extremely rare. We present a case of a suprapubic catheter misplaced in the left ureter leading to hydroureteronephrosis in a paediatric patient with history of complex pelvic fracture with urethral distraction defects after a motor vehicle accident. We highlight that emergent imaging evaluation and timely intervention saved us from the potential catastrophe.